2021
DOI: 10.2147/dddt.s320119
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Folic Acid Receptor-Targeted Drug Delivery System Based on Curcumin-Loaded β-Cyclodextrin Nanoparticles for Cancer Treatment

Abstract: Purpose A novel folate receptor-targeted β-cyclodextrin (β-CD) drug delivery vehicle was constructed to improve the bioavailability, biosafety, and drug loading capacity of curcumin. Controlled release and targeted delivery was achieved by modifying the nanoparticles with folic acid (FA). Methods Folate-conjugated β-CD-polycaprolactone block copolymers were synthesized and characterized. Curcumin-loaded nanoparticles (FA-Cur-NPs) were structured by self-assembly. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Additionally, in vitro cytotoxicity was proportional to cellular uptake efficiency and the in vivo marked accumulation in tumor site was responsible of greater antitumor activity. These findings indicated FA-CUR-NPs could represent a promising approach for improving cancer therapy through active targeting and controllable release [226]. Moreover, in another work the use of hydroxypropyl-β-CD as a carrier-solubilizer improved solubility of the curcumin-piperine system, its permeability through biological membranes (gastrointestinal tract, blood-brain barrier), the antioxidant and antimicrobial activities and as well as the enzymatic inhibition against acetylcholinesterase and butyrylcholinesterase [227].…”
Section: Curcumin/β-cyclodextrin and Solid Dispersions Formulationsmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, in vitro cytotoxicity was proportional to cellular uptake efficiency and the in vivo marked accumulation in tumor site was responsible of greater antitumor activity. These findings indicated FA-CUR-NPs could represent a promising approach for improving cancer therapy through active targeting and controllable release [226]. Moreover, in another work the use of hydroxypropyl-β-CD as a carrier-solubilizer improved solubility of the curcumin-piperine system, its permeability through biological membranes (gastrointestinal tract, blood-brain barrier), the antioxidant and antimicrobial activities and as well as the enzymatic inhibition against acetylcholinesterase and butyrylcholinesterase [227].…”
Section: Curcumin/β-cyclodextrin and Solid Dispersions Formulationsmentioning
confidence: 87%
“…Recently, a nano-drug system namely FA-CUR-NPs consisting of FA, β-CD, εCL and curcumin was performed to improve curcumin delivery in cervical cancer tissues which overexpress FRs and to achieve controllable release in vitro and in vivo. In this system, FA binding to FRs was used as a targeting molecule, β-CD modified by ε-CL as delivery carrier and for controlling drug release and curcumin as a model drug to limit multidrug resistance after administration [226]. The study demonstrated that in vitro curcumin release rate from FA-CUR-NPs under tumor microenvironment conditions (pH 6.4), was three times faster than that under systemic circulation conditions (pH 7.4).…”
Section: Curcumin/β-cyclodextrin and Solid Dispersions Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active targeting mode of nanoparticles depends upon the utilization of certain ligands like folate and transferrin, which bind to the proteins that are over-expressed or somewhat expressed on the target cellular sites [57]. This instigates the inbound folding of membranes and incorporates the nanoparticles into the cells through a phenomenon named receptor-mediated endocytosis (Figure 3).…”
Section: Active Targeting Of Nanoparticlesmentioning
confidence: 99%
“…However, its therapeutic efficacy is limited because of its poor solubility [ 5 ]. Several methods, such as the preparation of liposomes and nanoparticles [ 6 , 7 ] and self-microemulsion, have been used to increase the solubility and dissolution rate of insoluble drugs [ 8 , 9 , 10 , 11 ]. Solid dispersion (SD) can also efficiently increase the dissolution rate and solubility of insoluble drugs by changing the size and dispersion within the carrier.…”
Section: Introductionmentioning
confidence: 99%